Socio-Demographic and Clinical Characteristics of Adults With Psychotic Symptomatology Under Involuntary Admission and Readmission for Compulsory Treatment in a Referral Psychiatric Hospital in Cyprus - Kaikoushi, Katerina; Middleton, Nicos; Chatzittofis, Andeas; Bella, Evanthia; Alevizopoulos, Giorgos; Karanikola, Maria (Frontiers in Psychiatry, 2021)
Socio-demographic and clinical characteristics of adults under compulsory psychiatric treatment, have not been reported adequately in Southern European countries. We investigated the socio-demographic and clinical characteristics of adults with psychotic symptomatology who were involuntary treated in the acute Mental Health Services in Cyprus. A descriptive cross-sectional study was applied. Data collection (December 2016 to February 2018) achieved via a structured questionnaire including demographic and clinical variables. Census sampling was applied in Cyprus referral centre for compulsory psychiatric treatment. The sample included 406 individuals (262 males, 144 females). Approximately 86.2% were single, 77.6% were unemployed and 24.9% held a bachelor’s degree. The most frequent clinical diagnosis was schizophrenia or a relevant psychotic disorder (86.4%). The most frequent admission cause was non-adherence to pharmacotherapy along with disorganized behavior (agitation and/or self-care deficit, and/or aggressive behavior, and/or suicidal behavior) (53.6%). Moreover, 70.7% of the sample reported a positive personal history of mental health problems, while 42.1% reported a positive family history of mental health disorders. Half of the participants (52%) were previously involuntary admitted for compulsory treatment. Adjusted associations of readmission status were reported with Cypriot ethnicity (OR: 4.40, 95% CI: 2.58 – 7.50), primary education only (OR: 3.70, 95% CI: 1.64 – 8.37), readmission due to disorganized behaviour along with non-adherence to pharmacotherapy (OR: 10.84, 95% CI: 2.69 – 43.72), as well as along with substance use (OR: 6.39, 95% CI: 1.52 – 26.82). Readmission was almost five times more likely to occur due to suicidal behaviour (OR: 5.01, 95%CI: 1.09-22.99) compared to disorganized behaviour not otherwise specified. Additionally, those with a diagnosis of schizophrenia were more than 12 times more frequently readmitted for compulsory treatment compared to other diagnoses (OR 12.15, 95%CI: 1.04-142). Moreover, the participants with higher secondary education had 54,6% less odds to be involuntary re-admitted compared to Bachelor degree holders (OR 0.442, 95%CI: 0.24-0.79). A high percentage of involuntary treatment was noted due to non-adherence to pharmacotherapy and substance use. Re-evaluation of the effectiveness of relevant community interventions is suggested, as well as implementation of structured educational programs on therapy adherence during psychiatric hospitalization.